The indoor thermal climate in residential buildings after energy efficiency measures in a subarctic climate - Lundqvist, Petter (Luleå tekniska universitet, Energivetenskap, 2020)
There is ongoing work related to the energy efficiency of residential buildings in the subarctic regions in northern Sweden. The focus is often on the reduction of energy usage and the economic aspects for the property owners. With the introduction of new technology and changes to the existing building, the indoor thermal climate is affected. While these measures not necessarily create a negative impact on the occupants’ experience, it is essential to understand the outcome of various energy efficiency measures on an indoor thermal climate point of view. It is also crucial to explore used software, methods and how to interpret the outcome of projected simulations. The present thesis investigates residential buildings subjected to energy efficiency measures in the subarctic region of Sweden, primarily from an indoor thermal climate point of view. Both typical residential buildings in the region and a new pilot building with unconventional approaches were included. The goal of the present thesis was to establish important aspects of energy efficiency measures to improve the knowledge for the region. Along with measurements in the buildings, the building energy simulation software IDA Indoor Climate and Energy (IDA ICE) and the computational fluid dynamic (CFD) software ANSYS CFX were used in the present thesis. A comparison showed that the IDA ICE software and the CFX software gave different results when predicting the indoor thermal climate, mainly attributed to the thermal radiation. Due to the nature of CFD, the CFX was able to identify the variation of velocities, temperatures and thermal radiation in the whole volume, which also affected the results. Further, CFX could detect potential problems of the interior that could be crucial, that building energy simulation software such as IDA ICE could not. The results also demonstrate how CFD is an essential tool when evaluating the indoor thermal climate. When it comes to making a fair assessment of changes, it is important to consider the thermal parameters, the ...